Tunable light emission from chemical vapor deposited two-dimensional MoSe2 by layer variation and S incorporation - Singh, Vineeta; Late, Dattatray J.; Rath, Shyama (Journal of Vacuum Science & Technology A, 2020)
Mono- and few-layer thick MoSe2 and MoSxSe2-x domains were grown on insulating SiO2/Si substrates by chemical vapor deposition. Scanning electron microscopy and optical contrast images were used to determine the domain size and morphology. The structure, crystallinity, and the thickness (number of layers) of the as-synthesized domains were determined from Raman spectroscopy. The light emission was determined from photoluminescence (PL) spectroscopy. The PL emission started appearing only in domains having four layers or less, with the intensity increasing as the number of layers decreased. The PL peak position varied between 1.48eV (similar to 838nm) for four layers to 1.55eV (similar to 800nm) in the monolayer limit. Sulfur incorporation was done to enable a further tunability of the bandgap. The monolayer bandgap changed from 1.55eV for MoSe2 to 1.64eV (similar to 756nm) for MoS0.32Se0.68. The other effect of S incorporation was the formation of larger area domains in the alloy as compared to binary MoSe2 with an improvement in the structural properties, thus providing a pathway to improve the properties of two-dimensional semiconductors by mixing of two materials with similar atomic arrangements.